Should I stay or should I go—Medical assistants´ experiences and coping with patient demand and lack of appreciation during the Covid-19 pandemic - Anastasia Suslow; Kathrin Schlößler; Nino Chikhradze; Romy Lauer; Michael Pentzek; Achim Mortsiefer; Horst Christian Vollmar; Ina Carola Otte (PLoS ONE, 2025)
Background This article explores the psychological burden experienced by medical assistants (MAs) in General Practices during the Covid-19 pandemic (Corona virus disease 2019 (SARS-CoV-2)) in Germany. The study aims on demanding patient behavior, increased workload, and the perceived lack of appreciation and discuss their potential impact on the MAs´ well-being and career decisions. Methods A qualitative approach was utilized. MAs were included via a regional practice network as well as professional associations and newsletters. In total, 21 interviews with MAs from various federal states in Germany were conducted between April and September 2021. The semi-structured interview guideline focused on daily work challenges during the pandemic and its consequences. Interviews were recorded, transcribed, and analyzed using qualitative content analysis according to Kuckartz. Results The findings highlight core challenges, including demanding communication with patients, lack of appreciation in the media, a high workload, resilience versus career migration, and the needs and wishes of MAs in their everyday work. Abusive language, insults, and theft of materials by patients added significant stress. The interviews reveal how important teamwork and a supportive working environment are for overcoming these challenges. Conclusions The study underlines the urgent need for societal and political awareness regarding the challenges faced by MAs, especially during public health crises. The perceived social egoism in patient behavior, coupled with a lack of recognition and appreciation, contributed to a challenging work atmosphere and potential burnout risk. Recommendations include enhancing support for MAs, recognizing their contributions in the media, and fostering collaborative efforts between practitioners and policymakers to address the unique challenges in general practices. Trial registration German Register of Clinical Studies (DRKS) DRKS00032402; https://drks.de/search/de/trial/DRKS00032402 (Registration Date: 14.08.2023)